Media Literacy, Scientific Literacy, and Science Videos on the Internet - Rosenthal, Sonny (Frontiers in Communication, 2020)
Although video is not a new format for communicating about science, video-sharing platforms have democratized the process. Individuals who wish to share information or ideas about science can use these platforms to connect with potentially large and diverse audiences. This has benefits and drawbacks. The benefits are related to increased access to scientific information and greater public engagement with science. The drawbacks are related to communication within echo chambers and the spread of misinformation. This mini review discusses these benefits and drawbacks with respect to media and scientific literacies.